Etiology and pathophysiology of fibromyalgia - Ana Placida Marino Chamani Almanza; Dayani Silva da Cruz; Silvio Assis de Oliveira-Júnior; Paula Felippe Martinez (Revista Ciências em Saúde, 2023)
Fibromyalgia is a chronic condition of unknown etiology unrelated to specific laboratory markers for diagnosis because of poor etiopathogenesis. In general, the changes common to fibromyalgia are also seen in other chronic pain conditions, making the pathogenesis controversial among different pathological conditions. The unknown etiology makes the diagnosis difficult and consequently has repercussions on a not so effective treatment of patients with fibromyalgia. The restoration of systemic disorders provides a wide spectrum of therapeutic possibilities with the potential to guide professionals in establishing goals and evaluation methods. Therefore, this narrative review discusses the etiological and pathophysiological hypotheses involved in the development of fibromyalgia.